Development of the Japanese version of the Pediatric Quality of Life Inventory™ Transplant Module. Issue 1 (27th October 2016) - Kikuchi, Ryota; Mizuta, Koichi; Urahashi, Taizen; Sanada, Yukihiro; Yamada, Naoya; Onuma, Erika; Ono, Minoru; Endo, Miyoko; Sato, Iori; Kamibeppu, Kiyoko
Abstract: Background: Health‐related quality of life (HRQOL) is an important outcome in pediatric solid organ transplantation. Considering the emerging problems after transplantation, an evaluation of transplant‐specific aspects of HRQOL is essential, but no validated HRQOL measure is available in Japan. The aim of this study was therefore to develop the Japanese version of the Pediatric Quality of Life Inventory ™ (PedsQL) Transplant Module Child Self‐Report and to investigate its feasibility, reliability, and validity. Methods: Based on the PedsQL linguistic validation process, the Japanese version of the PedsQL Transplant Module was developed through translation and cognitive interviews (patient testing). The scale's reliability and validity were investigated, using statistical analyses of field tests of the target population. Results: Eighty‐seven pairs of pediatric liver‐transplant recipients and their parents participated in the field test. The pediatric patients completed the measure in 3–7 min, and the rate of missing items was low (0.27%). Excellent internal consistency and test–retest reliability were confirmed. Known‐groups validity, concurrent validity, and convergent and discriminant validity also were confirmed. Conclusions: Excellent feasibility, reliability, and validity of this Japanese self‐report version of the PedsQL Transplant Module Child Self‐Report were verified. As a measure of transplant‐specific aspects of HRQOL in Japanese pediatric patients who have undergone organ transplants, the Japanese version of the PedsQL Transplant Module is appropriate for use in clinical and research settings.